The Muslim world in modern South Asia : power, authority, knowledge - Robinson, Francis (State University of New York Press, 2020)
Sets out the challenges presented to Muslim societies by Western dominance over the past two hundred years, and explores Muslim responses, particularly in the context of South Asia.Over the past two hundred years, two great processes have shaped Muslim societies: Western domination and the industrial capitalism that came with it, and the Islamic revival that preceded the Western presence but came to interact significantly with it. In this book, Francis Robinson considers the challenges Western dominance has offered key aspects of Muslim civilization, particularly in the context of South Asia, which in the nineteenth century moved from being a receiver of influences from the rest of the Muslim world to being a transmitter of influences to it.Robinson also considers aspects of the Muslim revival and how they have come to shape, in various ways, Muslim responses to Western dominance. The role of the transmission of knowledge, both formal and spiritual, in forming Muslim societies is explored, and also the particular role of the transmitters in sustaining the Islamic dimensions of Muslim societies under Western dominance. Attention, too, is paid to the imposition of the modern state and the restriction of cosmopolitan spaces.Francis Robinson is Professor of the History of South Asia at Royal Holloway, University of London. His many books include Islam and Muslim History in South Asia; The 'Ulama of Farangi Mahall and Islamic Culture in South Asia; and Islam, South Asia, and the West.